Letter (copy) : International Trade Union Conference re Spain, etc. - Tewson, Vincent
012a-0014-001 Secretary's. HVT/FC/EK/304. TCJ/HJG/4. 24th November, 1938 Mr. G. M. Hann, National Amalgamated Union of Shop Assistants, Warehousemen and Clerks, Dilke House, Malet Street, London, W.C.1. Dear Mr. Hann, INTERNATIONAL TRADE UNION CONFERENCE RE SPAIN, ETC. I have your letter of the 22nd November in regard to the above matter which is being discussed at the meeting of the International Federation of Trade Unions and the Labour and Socialist International tomorrow. Mr. Hicks, the General Council's representative, has already left and I am sure full consideration will be given to the proposals put forward by the French Trade Unions. Yours sincerely, Assistant Secretary. 292/946/12a/14